Integrated transcriptomic and proteomic analysis reveals the complex molecular mechanisms underlying stone cell formation in Korla pear - Aisajan Mamat (Nature Portfolio, 2021)
Abstract Korla pear (Pyrus sinkiangensis Yü) is a landrace selected from a hybrid pear species in the Xinjiang Autonomous Region in China. In recent years, pericarp roughening has been one of the major factors that adversely affects fruit quality. Compared with regular fruits, rough-skin fruits have a greater stone cell content. Stone cells compose sclerenchyma tissue that is formed by secondary thickening of parenchyma cell walls. In this work, we determined the main components of stone cells by isolating them from the pulp of rough-skin fruits at the ripening stage. Stone cell staining and apoptosis detection were then performed on fruit samples that were collected at three different developmental stages (20, 50 and 80 days after flowering (DAF)) representing the prime, late and stationary stages of stone cell differentiation, respectively. The same batches of samples were used for parallel transcriptomic and proteomic analysis to identify candidate genes and proteins that are related to SCW biogenesis in Korla pear fruits. The results showed that stone cells are mainly composed of cellulose (52%), hemicellulose (23%), lignin (20%) and a small amount of polysaccharides (3%). The periods of stone cell differentiation and cell apoptosis were synchronous and primarily occurred from 0 to 50 DAF. The stone cell components increased abundantly at 20 DAF but then decreased gradually. A total of 24,268 differentially expressed genes (DEGs) and 1011 differentially accumulated proteins (DAPs) were identified from the transcriptomic and proteomic data, respectively. We screened the DEGs and DAPs that were enriched in SCW-related pathways, including those associated with lignin biosynthesis (94 DEGs and 31 DAPs), cellulose and xylan biosynthesis (46 DEGs and 18 DAPs), S-adenosylmethionine (SAM) metabolic processes (10 DEGs and 3 DAPs), apoplastic ROS production (16 DEGs and 2 DAPs), and cell death (14 DEGs and 6 DAPs). Among the identified DEGs and DAPs, 63 significantly changed at both the transcript and protein levels during the experimental periods. In addition, the majority of these identified genes and proteins were expressed the most at the prime stage of stone cell differentiation, but their levels gradually decreased at the later stages.